Determination of 4-(Methylnitrosamino)-1-(3-Pyridyl)-1-Butanone (NNK) arising from tobacco smoke in airborne particulate matter. (January 2022) - Aquilina, Noel J.; Havel, Christopher M.; Harrison, Roy M.; Ho, Kin-Fai; Benowitz, Neal L.; Jacob III, Peyton
Graphical abstract: Highlights: Airborne particulate matter (PM) is contaminated with the tobacco specific nitrosamine NNK. The atmospheric stability of NNK in comparison to airborne nicotine is reported. NNK is detected in PM in various geographic locations. NNK shows a seasonal variation. The load of NNK in PM10 is quantified. Abstract: The most important tobacco-specific nitrosamine found in cigarette smoke and formed in ageing smoke after cigarettes are extinguished is 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK). It is formed from nitrosation of nicotine, under particular conditions both in indoor and outdoor environments. NNK has been classified as a potent lung carcinogen which is expected to be found primarily in the particle-phase and to be stable in particulate matter. In this study tests have been carried out to show that a bisulfate-treated filter is more efficient than an untreated filter to collect both nicotine and NNK, and that the latter is stable in outdoor particulate matter. To characterize NNK in the outdoor environment, airborne samples were collected from 11 cities in USA, UK, Hong Kong and Malta with characteristics varying from low to high population densities and from urban to suburban to rural, and with desert characteristics and distinct climates. It has been shown that airborne particle + gas phase nicotine and particle-phase NNK behave in a linearly correlated manner. A seasonal analysis was carried out on a subset of data available from five sites in California, where the load of NNK in PM10 is driven by long range transport of the air masses passing over densely populated cities. In the winter season, the load of NNK in PM is higher than in summer in a statistically significant manner. The contamination of PM with NNK shows variability, but is observed at all sites. This paper highlights the potential risk of chronic exposure to NNK in particulate matter by the inhalation pathway.